Penegakan Hukum terhadap Anggota Polri yang Melakukan Tindak Pidana Narkotika - Gede Arya Aditya Darmika; Simon Nahak; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2019)
In the circulation of Narcotics and illegal drugs in Indonesia is very troubling and concern societies, and almost everything in the media airing the arrest of illicit traffic in Narcotics and other criminal acts. Similarly on the profession of policing, has a code of ethics that applies to the police and police functions. Code of ethics for the profession of policing is not only based on the requirements of professionalism, but also the normative basis has been set in Act 2 year 2002 Number of State police of the Republic of Indonesia that followed up with Regulations Assistant Police Number 7 Year 2006 Police Profession and Assistant Police Regulation Number 8 year 2006 regarding the Organization of work of the Commission and the code of ethics of the profession of the national police, so the Police Profession code of ethics binding applies to any members of the State police The Republic Of Indonesia. This research was analyze law enforcement by police in Narcotics criminal acts committed by members of the Police and the sanctions against members of the police who commit the crime of narcotics? The type of research used is type of normative legal research namely legal research conducted by way of examining the regulations associated with the Act No. 35 of the year 2009 about narcotics. After the legal materials acquired and collected, legal materials and then processed and analyzed with the legal arguments based on deductive logic of law-inductive (General-special). The authors can conclude that the matter of settlement of Narcotics made by police of the same with society in General through the judiciary. Dalam peredaran Narkotika dan obat terlarang di Indonesia sangat meresahkan dan memprihatinkan masyarakat, dan hampir setiap hal di dalam media ditayangkan penangkapan peredaran gelap Narkotika dan tindak pidana lainnya. Dalam menjalankan tugasnya sebagai penegak hukum kepolisian berpedoman kepada kode etik selaku pedoman pelaksanaan sehari-hari, pengaturan terkait kode etik kepolisian dapat dilihat dari UU Nomor 2 Tahun 2002 tentang Kepolisian Negara RI, Peraturan Kepala Kepolisian Republik Indonesia Nomor 8 Tahun 2006 dan Nomor 7 Tahun 2006. Masing-masing mengikat tentang pelaksanaan tugas keseharian kepolisian. Penelitian ini menganalisis penegakan hukum oleh kepolisian dalam Tindak Pidana Narkotika yang dilakukan oleh anggota Polri dan sanksi terhadap anggota polri yang melakukan Tindak Pidana Narkotika. Penelitian ini menggunakan tipe normatif yakni dengan melaksanaan penelitian hukum dengan mencermati peraturan perundang-undangan yang terkait dengan Undang-undang No. 35 Tahun 2009 tentang Narkotika. Setelah bahan penelitian diperoleh dan dikumpulkan, bahan tersebut kemudian diolah dan dianalisis dengan argumentasi hukum berdasarkan logika hukum deduktif-induktif (umum-khusus). Penulis dapat menyimpulkan bahwa perkara penyelesaian Narkotika yang dilakukan oleh kepolisian sama dengan masyarakat pada umumnya yaitu melalui peradilan umum.